THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE - Safriani, Lisda; Bakri, Mohammad Iqbal; Syafitri, Rahmi; Pattawe, Abdul (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study examines the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on financial performance in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2021–2024 period. The data used are in the form of secondary data from the annual report and sustainability report with a total of 98 observations compiled in the form of an unbalanced data panel. The study applies a quantitative approach utilizing panel data regression analysis, with data processed using EViews 14. The findings indicate that Good Corporate Governance (GCG) has a statistically significant effect with a negative direction on financial performance, while Corporate Social Responsibility (CSR) does not exhibit a statistically significant effect even though it has a positive direction. Simultaneously, the two variables also have no significant effect. These findings show that GCG and CSR have not been the main determinants in improving the company's financial performance. Keywords: Good Corporate Governanace, Corporate Social Responsibility, Financial Performance, Data Panel Regression, Unbalanced Data Panel